Assessment of focused ultrasound stimulation to induce peripheral nerve activity and potential damage in vivo - Rodríguez-Meana, Bruno; Santos-Nogueira, Eva; Trujillo-Vázquez, Sònia; Jakob, Anette; Udina, Esther; Fournelle, Marc; Navarro, Xavier (Frontiers in Neurology, 2024)
Introduction Peripheral neuroprostheses are aimed to restore loss of sensory and motor functions by interfacing axons in the peripheral nerves. Most common interfaces in neuroprostheses are electrodes that establish electrical connection with peripheral axons. However, some challenges arise related to long-term functionality, durability, and body response. Recently, focused ultrasound stimulation (FUS) has emerged as a non-invasive approach to modulate the nervous system. However, it is controversial whether FUS can induce axon depolarization. Methods We have assessed FUS applied in vivo to the rat peripheral nerve, with two objectives: first, to test whether FUS activates peripheral nerves under different stimulation conditions, and second, to evaluate if FUS inflicts damage to the nerve. FUS was delivered with three ultrasound transducers (Sonic Concept H115, H107, and H102) covering the largest set of parameters examined for FUS of peripheral nerves so far. Results We did not obtain reliable evoked action potentials in either nerves or muscles, under any FUS condition applied, neither over the skin nor directly to the nerve exposed. Additional experiments ex vivo and in vivo on mice, confirmed this conclusion. When FUS stimulation was applied directly to the exposed sciatic nerve, neuromuscular function decreased significantly, and recovered one week later, except for FUS at 0.25 MHz. Histologically, degenerating nerve fibers were observed, with a tendency to be higher with the lower FUS frequency. Discussion Past reports on the ability of ultrasound to stimulate the peripheral nerve are controversial. After testing a wide range of FUS conditions, we conclude that it is not a reliable and safe method for stimulating the peripheral nerve. Special consideration should be taken, especially when low-frequency FUS is applied, as it may lead to nerve damage.